43 REDUCED KIDNEY FUNCTION IS ASSOCIATED WITH POORER GLOBAL AND DOMAIN-SPECIFIC COGNITIVE PERFORMANCE IN COMMUNITY-DWELLING OLDER ADULTS. (18th November 2021) - Dyer, A; Laird, E; Hoey, L; Hughes, C; McNulty, H; Ward, M; Strain, J J; Molloy, A; Cunnningham, C; Sexton, D; McCarroll, K
Abstract: Background: Chronic Kidney Disease (CKD) is an important risk factor in the development of cognitive impairment. However, the association between reduced estimated Glomerular Filtration Rate (eGFR) and performance on domain-specific cognitive and neuropsychological assessments is less clear and may represent an important target in the promotion of optimal brain health in older adults. Methods: Participants from the Trinity, Ulster and Department of Agriculture cohort study underwent detailed assessment of cognitive and neuropsychological function using the Mini-Mental State Examination (MMSE), Frontal Assessment Battery (FAB) and Repeatable Battery for Assessment of Neuropsychological Status (RBANS). Mixed-effects Poisson and linear regression was used to assess the relationship between eGFR strata and cognitive/neuropsychological test performance. Results: 4, 887 participants were included (73.94 ± 8.25 years; 67.7% female). Reduced eGFR was associated with poorer performance on all three cognitive assessments, most pronounced in those with eGFR <45 mL/mL/1.73m 2 (IRR: 1.19; 95% CI: 1.09, 1.29; p < 0.001 for MMSE/IRR: 1.14; 95% CI 1.04, 1.24; p < 0.001 for the FAB/β: -3.23; 95% CI -5.18, −1.30; p = 0.001 for RBANS, fully adjusted). Reduced eGFR was associated with poorer performance on immediate memory, visual–spatial and attention RBANS domains. Associations were strongest in the youngest old (<70 years) with no association observed in those aged >80 years. Conclusion: Reduced kidney function was associated with poorer global and domain-specific function in community-dwelling older adults. Associations were strongest for those with eGFR <45 mL/min/1.73m 2 and the youngest-old, suggesting that this group may be most at risk and may benefit from potential preventative interventions.